2022
DOI: 10.3390/plants11030259
|View full text |Cite
|
Sign up to set email alerts
|

Seed Treatments with Microorganisms Can Have a Biostimulant Effect by Influencing Germination and Seedling Growth of Crops

Abstract: Seed quality is an important aspect of the modern cultivation strategies since uniform germination and high seedling vigor contribute to successful establishment and crop performance. To enhance germination, beneficial microbes belonging to arbuscular mycorrhizal fungi, Trichoderma spp., rhizobia and other bacteria can be applied to seeds before sowing via coating or priming treatments. Their presence establishes early relationships with plants, leading to biostimulant effects such as plant-growth enhancement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…japonicum and Bacillus strains, which were shown to have PGP activity, increased nodule number, total biomass, total nitrogen, and yield, under the conditions of low root zone temperatures [ 37 ]. Cardarelli et al [ 8 ] reported that the application of beneficial microorganisms to the seeds of the major crops resulted in increased germination, seedling vigor, biomass, and the ability to overcome stress both during and after emergence. Generally, seed bio-priming with PGPR improves seed quality, plant growth and stress tolerance through production of regulatory substances, nutrient enhancement, and plant protection [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…japonicum and Bacillus strains, which were shown to have PGP activity, increased nodule number, total biomass, total nitrogen, and yield, under the conditions of low root zone temperatures [ 37 ]. Cardarelli et al [ 8 ] reported that the application of beneficial microorganisms to the seeds of the major crops resulted in increased germination, seedling vigor, biomass, and the ability to overcome stress both during and after emergence. Generally, seed bio-priming with PGPR improves seed quality, plant growth and stress tolerance through production of regulatory substances, nutrient enhancement, and plant protection [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Problems in soybean seed quality occur during pre- and postharvest periods, and mostly include seed deterioration due to adverse environmental conditions, and seed diseases due to numerous pathogens [ 7 ]. In order to improve soybean seed quality, especially under stressful conditions and/or diseases, numerous researchers have explored different strategies, including pre-sowing seed treatments with beneficial microorganisms [ 8 ]. The development of microbial inoculants using plant growth-promoting rhizobacteria (PGPR) is increasingly regarded as an environmentally-friendly alternative to the extensive use of synthetic chemicals in agriculture [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms can be used in seed biopriming, using cyanobacteria ( Spirulina platensis ) can enhance maize's tolerance to cadmium via accelerated germination, restriction of Cd translocation, and improvement of photosynthetic electron flows and non‐photochemical quenching (Seifikalhor et al, 2020). The use of microorganisms in seed priming processes can effectively enhance plant performance by influencing germination rates and seedling growth (Cardarelli et al, 2022), thus enabling plants to cope better with heavy metal stress‐induced injuries (Figure 3).…”
Section: Enhanced Phytoextraction Of CD By Primingmentioning
confidence: 99%
“…Increasing agricultural crop productivity, especially cereals such as wheat, is relevant and extremely important [ 1 , 2 , 3 , 4 ]. One of the guiding principles of modern agricultural production is the introduction of environmentally sound and harmless approaches that are safe for human health [ 1 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%